Direct N-body simulation of the Galactic centre. Issue 3 (18th January 2019) - Panamarev, Taras; Just, Andreas; Spurzem, Rainer; Berczik, Peter; Wang, Long; Arca Sedda, Manuel
ABSTRACT: We study the dynamics and evolution of the Milky Way nuclear star cluster performing a high-resolution direct one-million-body simulation. Focusing on the interactions between such stellar systems and the central supermassive black hole, we find that different stellar components adapt their overall distribution differently. After 5 Gyr, stellar mass black holes are characterized by a spatial distribution with power-slope −1.75, fully consistent with the prediction of Bahcall–Wolf pioneering work. Using the vast amount of data available, we infer the rate for tidal disruption events, being 4 × 10 −6 per yr, and estimate the number of objects that emit gravitational waves during the phases preceding the accretion on to the super-massive black hole, ∼270 per Gyr. We show that some of these sources could form extreme mass-ratio inspirals. We follow the evolution of binary stars population, showing that the initial binary fraction of $5{{\ \rm per\ cent}}$ drops down to $2.5{{\ \rm per\ cent}}$ inside the inner parsec. Also, we explored the possible formation of binary systems containing a compact object, discussing the implications for millisecond pulsars formation and the development of Ia Supernovae.